Performance Analysis of Village Owned Enterprise Development Strategy in North Toraja Regency - Elisabet Pali; Isak Pasulu; Elsap Patta Pasulu; Johanna R. Tangirerung (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Village development is essential for enhancing community welfare and fostering economic independence in rural areas, yet many village-owned enterprises face operational challenges that hinder their sustainability. This study aims to analyze the development strategy of the Lembang-Owned Enterprise Maju Bersama in Lembang Sa’dan Ulusalu, Sa’dan District, North Toraja Regency, to support sustainable rural growth. A qualitative descriptive approach was employed, utilizing interviews, direct observations and document analysis. The findings reveal that the Lembang-Owned Enterprise benefits from a strong legal foundation and addresses community needs through its kiosk operations. However, weaknesses such as limited managerial skills, poor inventory management, and uncirculated capital due to unpaid loans impede progress. Opportunities include supportive government regulations and the region’s agricultural potential, while threats encompass low community participation and competition from external vendors. The study concludes that a Weakness-Opportunity strategy, focusing on capacity building and leveraging local resources, is critical for enhancing the enterprise’s performance. This research provides practical recommendations for improving managerial skills, community engagement, and partnerships to ensure the sustainability of village-owned enterprises in similar rural contexts.